2010
DOI: 10.14713/pcsp.v6i3.1041
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical Memory Narratives in Psychotherapy: A Coding System Applied to the Case of Cynthia

Abstract: Recent cognitive and psychodynamic oriented therapies have converged on the powerful role that narrative processing plays in psychotherapy. Although previous coding systems have examined specific aspects of memory narratives, there are no comprehensive methods for coding segments of clinical evaluations or psychotherapy sessions that zero in on the unit of a briefly recounted autobiographical memory narrative.   The present single case study aims to introduce and to demonstrate the Coding System for Autobiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…There is a growing interest in the concept of -narrative identity‖ and related processes or dimensions (McAdams & Pals, 2006;McLean, 2008) as tools to understand psychotherapy processes and change (Angus, Levitt & Hardtke, 1999;Angus et al, 2012;Boritz, Angus, Monette, Hollis-Walker, & Warwar, 2011;Luborsky, 1977;Matos, Santos, Goncalves, & Martins, 2009;Mendes et al, 2010;Singer, Blagov, Berry, & Oost, 2013;Singer & Bonalume, 2010a). Narrative identity is referred to as "the internal, dynamic life story that an individual constructs to make sense of his or her life" (Bauer, McAdams, & Pals, 2008).…”
Section: Abstract: Autobiographical Memory Narratives Borderline Pementioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing interest in the concept of -narrative identity‖ and related processes or dimensions (McAdams & Pals, 2006;McLean, 2008) as tools to understand psychotherapy processes and change (Angus, Levitt & Hardtke, 1999;Angus et al, 2012;Boritz, Angus, Monette, Hollis-Walker, & Warwar, 2011;Luborsky, 1977;Matos, Santos, Goncalves, & Martins, 2009;Mendes et al, 2010;Singer, Blagov, Berry, & Oost, 2013;Singer & Bonalume, 2010a). Narrative identity is referred to as "the internal, dynamic life story that an individual constructs to make sense of his or her life" (Bauer, McAdams, & Pals, 2008).…”
Section: Abstract: Autobiographical Memory Narratives Borderline Pementioning
confidence: 99%
“…The client is encouraged to recall and reflect on experiences, while the interviewer attends to associated emotional responses and uses follow-up questions that may offer opportunities to make connections across important experiences. This measure has been used in a single-case design (Singer & Bonalume, 2010a) and in unpublished research work with 30 clients (Bonalume, personal communication). The coding of emergent narratives was used to guide case conceptualization and the identification of metaphors and themes to assist the therapist in tracking the relationship dynamics within treatment.…”
Section: The Biopsychosocial Interview (Singer and Bonalume 2010a) Itmentioning
confidence: 99%
“…This is also important since SDMs are vital in everyday meaningful interactions and constitute the daily material for clinical interactions [14,39]. The narration of personal emotionally relevant experiences from the past is essential for the development of a worthwhile therapeutic alliance and for empathic sharing between the patient and the clinician [40].…”
Section: Resultsmentioning
confidence: 99%
“…They may also play a critical role in therapeutic contexts. In a series of studies, Singer and colleagues [12,13,14,7,15] showed that the analysis of SDM memories induced by psychotherapists or spontaneously evoked by patients during clinical interviews facilitates the formulation of the case as well as the choice of the most appropriate treatment [16]. On the other hand, though fragmentary, ECMs play a critical role in self-development across different life stages, by grounding relational and behavioural models.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at the exact prediction in Singer and Bonalume's (2010) article, their sometimes vague formulations seem to be a product of these degrees of freedom: "I would guess she attended roughly 30 sessions," or, "I think she might have had a tendency to come a little bit late" ( These predictions cannot be criticized for the rather vague content because in remaining so they take account of the above-described alternative progress lines the patient might take. Still, by predicting two possible outcomes, or sometimes vaguely suggesting one outcome (as in predicting attendance at the therapy sessions), the image is drawn that the client already brings all the criteria into the assessment and the analyst can, judging from the first assessment sessions, predict one (or at least two) possible directions.…”
Section: Clinical Predictions Based On Abmsmentioning
confidence: 99%